Identification of Mollusc Remains (Bivalve and Gastropod) from Archaeological Sites in Semporna, Sabah - Deejay Daxter A. Albert; Velat Bujeng; Stephen Chia (Tropical Life Sciences Research, 2022)
This paper discusses the identification of mollusc (bivalve and gastropod) remains from three archaeological sites in Semporna, Sabah, namely Bukit Tengkorak, Melanta Tutup and Bukit Kamiri, dated to the prehistoric period, from 3,000 to 800 years ago. Samples of mollusc remains used in this study were obtained from a series of archaeological excavations conducted at these three sites by the Centre for Global Archaeological Research, Universiti Sains Malaysia (CGAR, USM), Penang in collaboration with the Sabah Museum Department (SMD) from 1994 to 2007. In total, 90 taxa of molluscan species, of which 30 are bivalves and 60 are gastropods, had been identified. Out of 90, there were 55 taxa identified to the species level, of which 18 are bivalves and 37 are gastropods. They consisted mainly of marine species with small numbers of freshwater, brackish and terrestrial species. This study had provided new data and insights into the distribution and exploitation of molluscs by ancient human societies in different environments in Semporna, which will be useful not only for malacological research in the tropics but also for future biological and environmental studies in Sabah, Malaysia as well as for the Southeast Asian and Pacific regions.